Step
*
1
of Lemma
Raabe-test
1. x : ℕ ⟶ ℝ
2. lim n→∞.r(n) * x[n] = r0
⇒ (∃c:{c:ℝ| r0 < c} 
     ∃N:ℕ
      ((∀n:{N...}. ((r0 < r(n)) ∧ (r0 < x[n])))
      ∧ (∀n:{N...}. ((r0 < r(n)) ∧ (c ≤ ((r(n) * x[n]/x[n + 1]) - r(n + 1)))))))
⇒ Σn.x[n]↓
3. (∃N:ℕ
     ((∀n:{N...}. ((r0 < r(n)) ∧ (r0 < x[n])))
     ∧ (∀n:{N...}. (((r(n) * x[n]/x[n + 1]) - r(n + 1)) ≤ r0))
     ∧ Σn.(r1/r(N + n))↑))
⇒ Σn.x[n]↑
4. L : ℝ
5. ∀n:ℕ. (r0 < x[n])
6. lim n→∞.r(n) * ((x[n]/x[n + 1]) - r1) = L
7. r1 < L
8. k : ℕ+
9. (r1/r(k)) < (L - r1)
10. r0 < (L - r1 - (r1/r(k)))
⊢ lim n→∞.r(n) * x[n] = r0
BY
{ Assert ⌜lim n→∞.r(n) * ((r(n) * x[n]/r(n + 1) * x[n + 1]) - r1) = L - r1⌝⋅ }
1
.....assertion..... 
1. x : ℕ ⟶ ℝ
2. lim n→∞.r(n) * x[n] = r0
⇒ (∃c:{c:ℝ| r0 < c} 
     ∃N:ℕ
      ((∀n:{N...}. ((r0 < r(n)) ∧ (r0 < x[n])))
      ∧ (∀n:{N...}. ((r0 < r(n)) ∧ (c ≤ ((r(n) * x[n]/x[n + 1]) - r(n + 1)))))))
⇒ Σn.x[n]↓
3. (∃N:ℕ
     ((∀n:{N...}. ((r0 < r(n)) ∧ (r0 < x[n])))
     ∧ (∀n:{N...}. (((r(n) * x[n]/x[n + 1]) - r(n + 1)) ≤ r0))
     ∧ Σn.(r1/r(N + n))↑))
⇒ Σn.x[n]↑
4. L : ℝ
5. ∀n:ℕ. (r0 < x[n])
6. lim n→∞.r(n) * ((x[n]/x[n + 1]) - r1) = L
7. r1 < L
8. k : ℕ+
9. (r1/r(k)) < (L - r1)
10. r0 < (L - r1 - (r1/r(k)))
⊢ lim n→∞.r(n) * ((r(n) * x[n]/r(n + 1) * x[n + 1]) - r1) = L - r1
2
1. x : ℕ ⟶ ℝ
2. lim n→∞.r(n) * x[n] = r0
⇒ (∃c:{c:ℝ| r0 < c} 
     ∃N:ℕ
      ((∀n:{N...}. ((r0 < r(n)) ∧ (r0 < x[n])))
      ∧ (∀n:{N...}. ((r0 < r(n)) ∧ (c ≤ ((r(n) * x[n]/x[n + 1]) - r(n + 1)))))))
⇒ Σn.x[n]↓
3. (∃N:ℕ
     ((∀n:{N...}. ((r0 < r(n)) ∧ (r0 < x[n])))
     ∧ (∀n:{N...}. (((r(n) * x[n]/x[n + 1]) - r(n + 1)) ≤ r0))
     ∧ Σn.(r1/r(N + n))↑))
⇒ Σn.x[n]↑
4. L : ℝ
5. ∀n:ℕ. (r0 < x[n])
6. lim n→∞.r(n) * ((x[n]/x[n + 1]) - r1) = L
7. r1 < L
8. k : ℕ+
9. (r1/r(k)) < (L - r1)
10. r0 < (L - r1 - (r1/r(k)))
11. lim n→∞.r(n) * ((r(n) * x[n]/r(n + 1) * x[n + 1]) - r1) = L - r1
⊢ lim n→∞.r(n) * x[n] = r0
Latex:
Latex:
1.  x  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}
2.  lim  n\mrightarrow{}\minfty{}.r(n)  *  x[n]  =  r0
{}\mRightarrow{}  (\mexists{}c:\{c:\mBbbR{}|  r0  <  c\} 
          \mexists{}N:\mBbbN{}
            ((\mforall{}n:\{N...\}.  ((r0  <  r(n))  \mwedge{}  (r0  <  x[n])))
            \mwedge{}  (\mforall{}n:\{N...\}.  ((r0  <  r(n))  \mwedge{}  (c  \mleq{}  ((r(n)  *  x[n]/x[n  +  1])  -  r(n  +  1)))))))
{}\mRightarrow{}  \mSigma{}n.x[n]\mdownarrow{}
3.  (\mexists{}N:\mBbbN{}
          ((\mforall{}n:\{N...\}.  ((r0  <  r(n))  \mwedge{}  (r0  <  x[n])))
          \mwedge{}  (\mforall{}n:\{N...\}.  (((r(n)  *  x[n]/x[n  +  1])  -  r(n  +  1))  \mleq{}  r0))
          \mwedge{}  \mSigma{}n.(r1/r(N  +  n))\muparrow{}))
{}\mRightarrow{}  \mSigma{}n.x[n]\muparrow{}
4.  L  :  \mBbbR{}
5.  \mforall{}n:\mBbbN{}.  (r0  <  x[n])
6.  lim  n\mrightarrow{}\minfty{}.r(n)  *  ((x[n]/x[n  +  1])  -  r1)  =  L
7.  r1  <  L
8.  k  :  \mBbbN{}\msupplus{}
9.  (r1/r(k))  <  (L  -  r1)
10.  r0  <  (L  -  r1  -  (r1/r(k)))
\mvdash{}  lim  n\mrightarrow{}\minfty{}.r(n)  *  x[n]  =  r0
By
Latex:
Assert  \mkleeneopen{}lim  n\mrightarrow{}\minfty{}.r(n)  *  ((r(n)  *  x[n]/r(n  +  1)  *  x[n  +  1])  -  r1)  =  L  -  r1\mkleeneclose{}\mcdot{}
Home
Index